Contribution to knowledge of the distribution of Noctuoidea (Insecta: Lepidoptera) in Ukraine - Geryak, Yu. M.; Bezuglyi, S. K.; Gera, A. A.; Gleba, V. M.; Ivaniy, S. V.; Kanarskyi, Yu. V.; Kavurka, V. V.; Khalaim, Ye. V.; Kovalchuk, D. O.; Leshchenko, M. V.; Sergienko, V. M.; Suchkov, S. I.; et al. (The Kharkiv Entomological Society Gazette, 2023)
New records of 180 species of Noctuoidea from Ukraine are provided. Among them, one species, Hypenodes pannonica, is reported for the first time for Ukraine, and many species are recorded for the first time in certain regions: 92 — in Kirovograd Region, 13 — in Khmelnytskyi Region, 3 each — in Kharkiv and Poltava regions, 2 each — in Chernihiv, Lviv, and Rivne regions, and 1 each — in Cherkasy, Kyiv, Mykolaiv and Vinnytsia regions. In addition, new records for several local, rare and little-known species, with a distribution still insufficiently studied in Ukraine are presented. 1 fig., 18 refs.
Keywords: noctuoid moths; taxonomic composition; new records; fauna